2021
DOI: 10.3390/children8111054
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Clinical Atropine Use in Taiwanese Schoolchildren: Changes in Physiological Characteristics and Visual Functions

Abstract: Taiwan is commonly noted for its high prevalence of myopia, as well as a long history of more than 20 years of using atropine to control myopia. However, the clinical implications are rarely discussed. This is a cross-sectional study investigating the influence of topical atropine instillation on ocular physiology, visual function, and visual discomfort in children. Aged 7 to 12 years, 212 schoolchildren were recruited and divided into the atropine group and the non-atropine group. Physiological characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Previous studies have shown that the near heterophorias shifted in the exo direction after wearing the addition lenses, 28,29 and our work published in 2021 also indicated that the heterophoria tended to be more exo in participants receiving atropine, compared with the controls 13 . The results of the present study showed that heterophorias measured at the Harmon distance through the near addition were significantly more exo (−3.90 ± 4.91△) than with the distance correction (2.91 ± 5.62△; p < 0.0001).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Previous studies have shown that the near heterophorias shifted in the exo direction after wearing the addition lenses, 28,29 and our work published in 2021 also indicated that the heterophoria tended to be more exo in participants receiving atropine, compared with the controls 13 . The results of the present study showed that heterophorias measured at the Harmon distance through the near addition were significantly more exo (−3.90 ± 4.91△) than with the distance correction (2.91 ± 5.62△; p < 0.0001).…”
Section: Discussionsupporting
confidence: 62%
“…Subjects with a high lag of accommodation and esophoria have been reported to show better efficacy of myopia control by using bifocal or multifocal spectacle lenses; 28,29 therefore, it is recommended to include a heterophoria test as part of the routine examination at the follow‐up visits. Furthermore, for children treated with medium or high concentrations of topical atropine, the stereopsis and NPC test could be useful to screen possible binocular vision anomalies 13 . The participants reported adherence to wearing the PAL and their visual function was significantly improved, thus supporting the combination of PAL+ atropine therapy, particularly for children who received higher doses of atropine to slow down fast myopic development.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies showed that pupil size showed different changes according to the concentration of atropine in the eye drops; thus, we propose that the optical quality may have decreased because of the change in pupil diameter. [ 21 22 23 ]…”
Section: Discussionmentioning
confidence: 99%